Bulgarin and others. 3. F.V. Bulgarin’s Letters to Censors - Abram I. Reitblat (Литературный факт, 2017)
The article presents F.V. Bulgrins letters (dd. 1829-1849) to censors in St.-Petersburg, who examined the materials of Severnaya Pchela and Bulgarin’s multi-volume “Recollections”. The letters published herewith help to better understand both Bulgarin’s complicated relations with the censorship apparatus, and the attitude of the state to the press and the fledgling public opinion in the epoch of Nikolay I.